Lack of clinically relevant differences in safety and pharmacokinetics after second‐dose administration of intranasal diazepam within 4 h for acute treatment of seizure clusters: A population analysis. Issue 7 (19th April 2022) - Cascino, Gregory D.; Tarquinio, Daniel; Wheless, James W.; Hogan, Robert Edward; Sperling, Michael R.; Desai, Jay; Vazquez, Blanca; Samara, Emil; Misra, Sunita N.; Carrazana, Enrique; Rabinowicz, Adrian L.
Abstract: Objective: Current diazepam nasal spray labeling requires waiting 4 h before administering a second dose. The objective of the current analyses was to examine safety and pharmacokinetic profiles of second doses of diazepam nasal spray given 0−4 h after the first dose. Methods: Two datasets were analyzed. The first, a long‐term, repeat‐dose safety study of diazepam nasal spray, compared rates of treatment‐emergent adverse events (TEAEs), serious TEAEs, and treatment‐related TEAEs for patients receiving ≥1 second dose ≤4 h versus all second doses >4 h after the first. The second was a population pharmacokinetic analysis using data from three phase 1 studies to model drug exposure when a second dose of diazepam nasal spray was administered across multiple time points (1 min−4 h) following the first dose. Results: In the repeat‐dose safety study, a second dose of diazepam nasal spray was administered ≤24 h after the first to treat 485 seizure clusters in 79 patients. Rates of TEAEs were similar between patients receiving ≥1 second dose in ≤4 h (89.5%, n  = 38) compared with >4–24 h only (80.5%, n  = 41). The most common treatment‐related TEAEs were associated with nasal discomfort, which was mild or moderate and transient. There were no reports of respiratory or cardiac depression. The pharmacokinetic simulations of second doses predicted comparable elevations of plasma diazepam concentrations with administrations across a range of intervals after the first dose (1 min−4 h). Significance: These data indicate that the safety and pharmacokinetic profiles of a second dose of diazepam nasal spray administered within 4 h of the first dose are consistent with those associated with current labeling. This is potentially important for patients with seizure clusters who have a recurrent seizure within 4 h of first treatment and might benefit from immediate retreatment to reduce the risk of progression to status epilepticus.